A rapid access to substituted oxazoles via PIFA-mediated oxidative cyclization of enamides. Issue 9 (2nd March 2017) - Kamiya, Midori; Sonoda, Motohiro; Tanimori, Shinji
Abstract: A facile and rapid access to multi-substituted oxazoles has been achieved under mild reaction conditions in a short reaction time. Reaction of enamides1 with [bis(trifluoroacetoxy)iodo]benzene (PIFA) in trifluoroethanol (TFE) at room temperature for 15 min afforded the desired oxazoles2 in moderate to excellent yields (58–98%). A wide range of functional group tolerance has been observed for these transformations. Graphical abstract: